Implementation of Kurikulum Merdeka for Learning History Subjects for Students of State Vocational High School Number 2 In Kayuagung - Tomy Wijaya; Andika; Syarifuddin (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
Curriculum reform is an important part of Indonesia's education development efforts. In this regard, there have been many changes in the Indonesian education system, including improvements in curriculum, teaching methods, use of infrastructure, and the quality of teachers as educators. The Ministry of Education, Culture, Research, and Technology in 2022 has issued a policy that has given students freedom to hone their abilities in the Merdeka Curriculum. The implementation of the Merdeka Curriculum at State Vocational High School Number 2 in Kayuagung is new and requires an implementation process because it is difficult for teachers to find time for effective teaching and learning. This research emphasizes natural sources of information, uses snowball data collection, and uses triangulation to obtain information. Informative research is directional/qualitative, which is more general in nature. The concept of Merdeka curriculum for history subjects at State Vocational High School Number 2 in Kayuagung is directed learning planning, mastery of skills, efficient use of time, and creativity. The aim is to create an environment and openness through debate between teachers and students, and to improve students' abilities. The curriculum also emphasizes ethical behavior, soft and hard skills, and scientific understanding. It promotes freedom to learn, demands creativity from educators, and encourages independence, creativity and flexibility.